2017
DOI: 10.1002/2015wr017548
|View full text |Cite
|
Sign up to set email alerts
|

Soil moisture background error covariance and data assimilation in a coupled land‐atmosphere model

Abstract: This study characterizes the space-time structure of soil moisture background error covariance and paves the way for the development of a soil moisture variational data assimilation system for the Noah land surface model coupled to the Weather Research and Forecasting (WRF) model. The soil moisture background error covariance over the contiguous United States exhibits strong seasonal and regional variability with the largest values occurring in the uppermost soil layer during the summer. Large background error… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 84 publications
1
20
0
Order By: Relevance
“…The B matrix contains information about the weights of the control states and multivariate error correlation, which allows the spread of the information from the observations to the control states with balance (Bannister 2008a,b). Similar to Lin et al (2017b), this study uses the NMC method (Parrish and Derber 1992) to compute the B matrix:…”
Section: B Formulation Of Variational Data Assimilation and Background Error Covariance Estimationmentioning
confidence: 99%
See 2 more Smart Citations
“…The B matrix contains information about the weights of the control states and multivariate error correlation, which allows the spread of the information from the observations to the control states with balance (Bannister 2008a,b). Similar to Lin et al (2017b), this study uses the NMC method (Parrish and Derber 1992) to compute the B matrix:…”
Section: B Formulation Of Variational Data Assimilation and Background Error Covariance Estimationmentioning
confidence: 99%
“…This approach has been tested and is operational in a land surface model coupled to Météo-France's Aire Limitée Adaptation Dynamique Développement International (ALADIN) limited area model (Draper et al 2009(Draper et al , 2011Mahfouf 2010;Mahfouf and Bliznak 2011;Parrens et al 2014;Schneider et al 2014;Duerinckx et al 2017) and the Integrated Forecast System at ECMWF (Drusch et al 2009;De Rosnay et al 2013). In addition, several studies have developed a coupled data assimilation system with the Weather Research and Forecasting (WRF) Model to assimilate soil moisture information (Rasmy et al 2011(Rasmy et al , 2012Santanello et al 2016;Seto et al 2016;Lin et al 2017a). Nonetheless, none of these studies addresses the problems in strongly coupled data assimilation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Commonly, uncertainties in representing land use, soil moisture (SM), and terrain conditions on the underlying surface, which affect the land-atmosphere interaction directly, are identified as the major sources of error in near-surface weather forecasting (Cheng & Steenburgh, 2005;Massey et al, 2014;Zhang et al, 2013). Hence, the impacts of underlying surface characteristics and bias corrections on NWP have been investigated in recent years (e.g., Fan & van den Dool, 2011;Massey et al, 2016;Chen et al, 2017;Lin et al, 2017). Results indicated that the bias correction of SM could help the near-surface temperature prediction in those case studies.…”
Section: Introductionmentioning
confidence: 99%
“…The Earth's vegetation, and thus the global food security, depends on the soil moisture climatology [2]. Trends in intensity, frequency and duration of the global precipitation [3], resulting from a changing climate, makes monitoring of soil moisture a key factor to extend forecast skill of land-atmosphere models [4,5]; improve drought modeling and management [6,7]; and further unravel processes that regulate evapotranspiration [8,9], as well as carbon [10] and nitrogen cycles [11].…”
Section: Introductionmentioning
confidence: 99%